2020
DOI: 10.1177/1475090220972586
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of impact damage caused by dropped objects on floating offshore structures

Abstract: Offshore facilities are exposed to the risk of accidental damages caused by fire, explosion, dropped objects, extreme environmental events and vessel collision poses a big threat to the safety and operation. During any lifting work, either from a supply vessel to the installation or from within the installation or plant itself, there is a potential danger when objects are being lifted for a dropped object accident to take place. This paper introduces extensive dropped object analyses applied in the design of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Trong quá trình hoạt động, bên cạnh các trường hợp tải trọng bình thường, các tàu container cũng phải đối mặt với các tai nạn bất ngờ có liên quan đến va đập, mắc cạn, hỏa hoạn, kể cả các vật thể rơi tự do trên boong. Trường hợp vật rơi trên boong có thể xảy ra khi xuất hiện sự cố của hệ thống cẩu trong quá trình bốc dỡ các hàng hóa container trên tàu khi cập cảng hoặc xuất bến [1]. Các tai nạn này là nguyên nhân gây ra thiệt hại nghiêm trọng đến độ bền của con tàu, có thể gây ô nhiễm môi trường, tốn kém về chi phí sửa chữa, làm thủng các khoang chứa hoặc thậm chí đe dọa đến tính mạng con người [2].…”
Section: đặT Vấn đềunclassified
“…Trong quá trình hoạt động, bên cạnh các trường hợp tải trọng bình thường, các tàu container cũng phải đối mặt với các tai nạn bất ngờ có liên quan đến va đập, mắc cạn, hỏa hoạn, kể cả các vật thể rơi tự do trên boong. Trường hợp vật rơi trên boong có thể xảy ra khi xuất hiện sự cố của hệ thống cẩu trong quá trình bốc dỡ các hàng hóa container trên tàu khi cập cảng hoặc xuất bến [1]. Các tai nạn này là nguyên nhân gây ra thiệt hại nghiêm trọng đến độ bền của con tàu, có thể gây ô nhiễm môi trường, tốn kém về chi phí sửa chữa, làm thủng các khoang chứa hoặc thậm chí đe dọa đến tính mạng con người [2].…”
Section: đặT Vấn đềunclassified
“…The energy absorption properties of structures in accidental loads can be calculated by integrating the area below the accidental force-deformation curve. Ozguc [23] performed a drop object study to identify the effect of dropping heavy items on the floating production storage and offloading (FPSO) hull structure. The drop object impact analyses showed that even though certain structural members were permanently deformed by drop loads, failure did not occur in accordance with the plastic strain criteria outlined in NORSOK standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During operations, in addition to standard load cases, container ships face unexpected accidents related to collisions, grounding, fires, and even falling objects on the deck. For example, falling objects on the deck can occur when the crane system malfunctions while loading and unloading container cargo on the ship while in port or during departure [1]. These accidents are the causes of severe damage to the vessel's structural integrity, which can result in environmental pollution, costly repairs, punctured cargo holds, or even endanger human lives [2].…”
Section: Introductionmentioning
confidence: 99%